Compensation as a means to justice? : Sexual violence survivors’ views on the tort law option in Iceland - Antonsdottir, Hildur Fjola (Feminist Legal Studies, 2020)
Limited attention has been paid to the potential of tort law to address the harm of sexual violence. Based on interviews with 35 victim-survivors of sexual violence in Iceland, this study asks: How do victim-survivors understand monetary compensation? How can tort law meet victim-survivors’ justice interests? The findings suggest that in addition to the financial risk involved, most participants had ambivalent views towards pursuing and receiving monetary compensation. Many thought that, given their often extensive pecuniary and non-pecuniary losses, it was only fair to receive compensation; but at the same time, they did not want to accept ‘dirty money’ they considered that pursuing monetary compensation could undermine their credibility, and monetary compensation only partially aligned with their ideas about justice. The findings are interpreted in the context of tort law theory, taboo trade-offs and survivor-centred justice. It is suggested that state intervention is needed to better meet victim-survivors’ justice interests.